Screening of Keratinolytic Bacteria from Poultry Wastes - Jahan, Z; Khan, SN; Hoque, M Mozammel (Bangladesh Journal of Scientific and Industrial Research, 2010)
The aim of this study was to characterize keratinolytic bacteria isolated from feather waste. Six isolates were recovered from poultry feather- decomposed materials. Isolate Z3 and Z4 showed important feather degrading activity when grown on basal medium containing 1% native feather as the only source of energy, carbon and nitrogen. All isolates were Gram positive and rod-shaped bacilli. Based on microscopic and biochemical analysis, the isolates were identified as Bacillus spp. Keratinolytic activities of these isolates were measured after cultivation of the bacteria on raw feathers. Maximum keratinase activity was showed by the isolate Z4 (22.3 U/ml) with the specific activity of 40.5 U/mg. Bacillus sp. Z4 is a potent producer of keratinase, which can be used for production of the enzyme in large scale. Key words: Identification; Purification; Characterization; Keratinase; Feather DOI: 10.3329/bjsir.v45i3.6535 Bangladesh J. Sci. Ind. Res. 45(3), 261-266, 2010